Desenvolvimento de membranas poliméricas para sistemas de remediação de íons metálicos pesados em soluções aquosas - Bosquetti, João César (2019)
The planet Earth is flooded with about 1.4 billion km3 of water, meaning that almost 71% of its surface is covered by water. However, only about 0.77% of this volume is accessible in the form of fresh water presented in rivers, lakes, groundwater and the atmosphere. Meanwhile of this small amount, about 12.8% have been contaminated or poorly used by man. This contamination is usually caused by percolation, whether of spot or diffuse, such as accidents in reservoir tanks, discharge of sewage sludge, improper use of fertilizers and sanitary waste, as well as accumulation of waste on riverbanks, has been increasing in last years. Contamination of water by heavy metals is perhaps the most worrying of contaminations, since they are highly toxic, cumulative and difficult to mitigate. In this sense, considering the amount of residues generated in the Laboratory of Teaching of Inorganic Chemistry, contaminated with heavy metals of high toxicity, it was thought of a way to reduce the amount of ions of some metals, especially lead (Pb), cádmium (Cd) and Mercury (Hg), employing low cost and easy to obtain polymer membranes to minimize the amount of waste sent to the Department of Waste Management (DeGR) of the Federal University of São Carlos - UFSCar. The aim is to minimize these ions present in the solutions, bringing the possibility of reuse of previously contaminated water or to discard it in the common domestic sewage, depending on the efficiency generated by the adsorption yield of these membranes in removing these inconvenient ions from the aqueous solution of discard. Basically, high density polyethylene (HDPE) membranes were modified with polyethylene with maleic anhydride (PE-g-AM), loaded with sodium aluminate and incorporated with aluminum phosphate (AlPO4). Membranes were synthesized whose proportions of these materials were varied with the purpose of verifying which of them would give the best yield. In this aspect, it was observed that all the membranes and blends synthesized showed heterogeneity in their constitution, resulting in regions with higher and lower yield in the same membrane. However, the blends loaded and incorporated with aluminum phosphates had a slightly higher adsorption efficiency compared to ions dispersed in the solution.